2020
DOI: 10.3390/coatings10050443
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Charged Ti Nanoparticles and Their Deposition Behavior with a Substrate Bias during RF Magnetron Sputtering

Abstract: This study is based on the film growth by non-classical crystallization, where charged nanoparticles (NPs) are the building block of film deposition. Extensive studies about the generation of charged NPs and their contribution to film deposition have been made in the chemical vapor deposition (CVD) process. However, only a few studies have been made in the physical vapor deposition (PVD) process. Here, the possibility for Ti films to grow by charged Ti NPs was studied during radio frequency (RF) sputtering usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
2
4
0
Order By: Relevance
“…At the same time, they will be repelled by the substrate with the bias of +50 V, decreasing the number density of Ti NPs captured on the TEM membrane (Figure 3c,f). In agreement with these results, Kwon et al reported that the positively charged Ti NPs were generated during Ti RF sputtering [32]. The strong dependence of the number density of Ti NPs on the electrical bias in Figure 3 indicates not only that some of the Ti NPs are electrically charged but also that they were formed in the gas phase instead of being nucleated on the TEM membrane.…”
Section: Capturing Charged Nps With Various Pressure During Rf Sputtering With a Ti Targetsupporting
confidence: 73%
See 3 more Smart Citations
“…At the same time, they will be repelled by the substrate with the bias of +50 V, decreasing the number density of Ti NPs captured on the TEM membrane (Figure 3c,f). In agreement with these results, Kwon et al reported that the positively charged Ti NPs were generated during Ti RF sputtering [32]. The strong dependence of the number density of Ti NPs on the electrical bias in Figure 3 indicates not only that some of the Ti NPs are electrically charged but also that they were formed in the gas phase instead of being nucleated on the TEM membrane.…”
Section: Capturing Charged Nps With Various Pressure During Rf Sputtering With a Ti Targetsupporting
confidence: 73%
“…One possible way to determine which of the small neutral NPs and atoms is a dominant flux for film deposition would be studying the crystallinity of the film deposited under the positive bias. A similar study was conducted by Kwon et al [32]. The results will be shown later.…”
Section: Capturing Charged Nps With Various Pressure During Rf Sputtering With a Ti Targetsupporting
confidence: 63%
See 2 more Smart Citations
“…However, an electric bias in these techniques would be used toward the anode, which can overlap within the plasma or require complicated and costly requirements. So the DC sputtering technique can be considered a simple and low cost to obtain metal's and alloy's thin films [24]. In the physical vapor deposition (DC sputtering process), an electron is accelerated from the cathode toward the argon atom and collide with it to produce the argon ion, this ion has a positive charge, so it will attract toward the cathode to eject an atom from the target toward the substrate.…”
Section: Introductionmentioning
confidence: 99%